Hubungan antara Perilaku Enam Pesan Kunci dengan Kejadian Stunting pada Anak dibawah Dua Tahun di Provinsi Jawa Tengah: Association between Six Key Messages Behaviour and Incidence of Stunting in Under-Two-Year-Old Children in Central Java Province - Kartasurya, Martha Irene; Asna, Alfi Fairuz; Denny, Hanifa Maher; Nuridzin, Dion Zein; Dharmawan, Ligar Tresna (Universitas Airlangga, 2024)
Background: The stunting prevalence in Central Java Province remains high. Six key messages, i.e. iron tablet supplementation, healthy latrines, exclusive breastfeeding, Integrated Health Care Post (Posyandu) visit, hand washing, and Antenatal Care visit are the efforts to reduce the prevalence of stunting. Objectives: This study aimed to analyse the relationship between the behaviour of the six key messages and the stunting prevalence in four districts of Central Java Province. Methods: This cross-sectional study was conducted in Brebes Regency, Tegal Regency, Banyumas Regency, and Semarang City with 424 mothers who have under two-year-old children randomly selected as sample. Data were collected by interview using a structured questionnaire with the results grouped into attitude and practices categories. The body’s weight and length were measured by a digital scale and infantometer. Data were analysed using the chi-square test. Results: The findings indicated that 21.5% of children under two had stunting. Besides, behaviour regarding six key messages were mostly good. There was no association between mothers' iron tablet consumption behaviour and the nutritional status of under-two children. There was an association between maternal attitudes about exclusive breastfeeding and knowledge about hand washing with length for age index (p=0.004). There was also an association between antenatal care and Posyandu visits practice with weight for age index (p=0.004 and 0.018). There was a relationship between attitude regarding the use of latrines and the weight for length index (p=0.001). Conclusions: Only the key messages of exclusive breastfeeding attitude, antenatal care visit practice, Posyandu visit practice, and hand washing attitude were associated with the nutritional status of under-two children.